2009
DOI: 10.3324/haematol.2009.005827
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced globin chain synthesis determines erythroid cell pathology in thalassemic mice

Abstract: Background β-thalassemia occurs from the imbalanced globin chain synthesis due to the absence or inadequate β-globin chain production. The excessive unbound α-globin chains precipitate in erythroid precursors and mature red blood cells leading to ineffective erythropoiesis and hemolysis. Design and MethodsIn vitro globin chain synthesis in reticulocytes from different types of thalassemic mice was performed. The effect of imbalanced globin chain synthesis was assessed from changes of red blood cell properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
5
27
0
1
Order By: Relevance
“…The genotype of each mouse was verified from the tail DNA. The heterozygous b IVSII-654 knockin mouse had a phenotype of b-thalassemia intermedia, which was consistent to the previous report (Lewis et al 1998;Srinoun et al 2009), whereas the homozygous genotype was lethal. The animals were acclimatized in the husbandry unit (polystylene shoebox cages) with room temperature of 25°C and humidity of 55% for at least 7 days under 12/12 h dark-light cycle, and were fed regular chow (containing 1.0% calcium and 0.9% phosphorus) and distilled water ad libitum.…”
Section: Animalssupporting
confidence: 90%
“…The genotype of each mouse was verified from the tail DNA. The heterozygous b IVSII-654 knockin mouse had a phenotype of b-thalassemia intermedia, which was consistent to the previous report (Lewis et al 1998;Srinoun et al 2009), whereas the homozygous genotype was lethal. The animals were acclimatized in the husbandry unit (polystylene shoebox cages) with room temperature of 25°C and humidity of 55% for at least 7 days under 12/12 h dark-light cycle, and were fed regular chow (containing 1.0% calcium and 0.9% phosphorus) and distilled water ad libitum.…”
Section: Animalssupporting
confidence: 90%
“…Oxidative damage occurs in erythroid cells of ␤-thalassaemic mice that contain elevated levels of unpaired ␣Hb (21)(22)(23)(24). Kong et al (6) showed similar increases in reactive oxygen species in AHSP Ϫ/Ϫ mice, suggesting that AHSP has a role in limiting reactive oxygen species production during normal erythropoiesis.…”
Section: Adult Human Hemoglobin (Hb)mentioning
confidence: 81%
“…Tail DNA was used to verify the genotype of each mouse. The phenotype of hemizygous ␤ IVSII-654 mice was categorized as ␤-thalassemic intermedia with iron deposition in the heart and liver, and imbalanced globin synthesis with ␣-to-␤-globin ratio of 1.26 (19,24,26). The homozygous ␤ IVSII-654 genotype is lethal, and the fetus usually dies in utero.…”
Section: Animalsmentioning
confidence: 99%